The Role of Container Security Initiative (CSI) in Improving Supply Chain Security in Indonesia - Rizkiyani, Hasna Moraina; Trismadi, Trismadi; Supriyadi, Asep Adang (Formosa Journal of Applied Sciences, 2024)
The Container Security Initiative (CSI) is a pivotal program in enhancing global supply chain security, particularly in Indonesia. Introduced as a response to terrorist threats post-September 11, 2001, CSI aims to secure international container shipments through pre-screening at ports of origin. This article analyzes CSI implementation in Indonesia, its impact on supply chain security, and its role in bolstering maritime security. CSI has proven effective in mitigating smuggling risks and improving logistical efficiency. The program also fosters international cooperation in addressing transnational threats. Despite challenges such as increased operational costs, CSI contributes significantly to Indonesia's national security and economic stability. Effective CSI implementation has the potential to strengthen Indonesia's position in global trade and enhance resilience against maritime security threats.